Utilization of agro-industrial by-products as substrates for dextransucrase production by Leuconostoc mesenteroides T3: Process optimization using response surface methodology - Miljković Miona G.; Davidović Slađana Z.; Đukić-Vuković Aleksandra P.; Ilić Mila V.; Simović Milica B.; Rajilić-Stojanović Mirjana D.; Dimitrijević-Branković Suzana I. (Hemijska Industrija, 2021)
Dextransucrase (DS) is a glucosyltransferase (E. C. 2.4.1.5) that catalyzes the transfer of glucosyl residues from sucrose to dextran polymer and liberates fructose. This enzyme isassociated with a wide application range of dextran and oligosaccharides. DS production by Leuconostoc mesenteroidesT3 was optimized using a Central Composite Design under the Response Surface Methodology. Three variables were chosen for optimization: distillery stillage, sucrose and manganese concentration. The results showed that sucrose and manganese concentrations had a positive linear effect on DS production while all variable interactions (stillage-manganese, stillage-sucrose, and sucrose-manganese) had significant influences on the DS production. The maximal DS yield of 3.391±0.131 U cm-3, was obtained in the medium with 64.33 % distillery stillage concentration, 5.30% sucrose concentration and 0.022 % manganese concentration. Our study revealed the potential of distillery stillage combined with sugar beet molasses, supplemented with sucrose and manganese to be employed as a valuable medium growth for lactic acid bacteria and production of DS. Also, taking into consideration the origin of the substrates, utilization of industrial by-products in this way has a great environmental relevance and is in accordance with circular economy.